Penerapan Metode Bermain Peran Dalam Meningkatkan Ketrampilan Bahasa Inggris Pada Anak Usia Dini - Erni Andriya Ningsih; Bambang Harmanto; Muhammad Azam Muttaqin (Jurnal Kajian Anak (J-Sanak), 2024)
The purpose of this study is to find out how the role play method can be applied to improve the English language skills of young children in Kindergarten Group B of Bakalani Village, Purwantoro District, Wonogiri Regency. This study was conducted in Purwantoro District Bakalan Village Kindergarten, the number of subjects was 19 children, 10 of which were 5-6 years old boys and 9 were girls. This research method uses classroom action research. This study was conducted in 3 cycles and each cycle was conducted in two meetings. The research data collection techniques are observation and speaking skills tests. Meanwhile, the data analysis technique used in this study is a descriptive statistical analysis method that uses percentages. Based on research findings and data analysis, the role-playing method can improve students' #039; English language skills. This can be seen in the survey on the classroom performance of the students in the first session and#039; The knowledge of the English language is only 16% or still classified as very poor. After that, continuing in cycle II, students and#039; English proficiency increased to 44 percent or was still classified as poor. Then in cycle III, the increase was 78% or classified as good.